TLSO: The Effect of Spinal Translation on Initial Coronal Curve Correction, Lateral Trunk Shift, and Coronal Balance in Adolescent Idiopathic Scoliosis. Issue 2 (April 2022) - Falbo, Kierra J.; Hutchinson, Sara; Kelly, Megan; Peethambaran, Ammanath
ABSTRACT: Introduction: Adolescent idiopathic scoliosis is often treated orthotically with thoracic lumbar sacral orthoses (TLSOs). The goal of these TLSOs is to improve the scoliotic curve during wear to prevent further curve progression. To achieve this in-orthosis curve improvement, clinicians often apply corrective modifications to a 3D model of the patient's trunk through computer-aided design (CAD) software, which are fabricated into the TLSO. Modifications often include laterally shifting certain portions of the orthosis to apply corrective forces to the scoliotic curve. The amount and magnitude of the shifting applied are loosely based on clinical experience and patient characteristics, but the decision is somewhat arbitrary. The purpose of this study is to determine any existing correlation between applied coronal translation (shift) through CAD modifications of TLSOs and resulting coronal curve correction in female subjects with idiopathic scoliosis. Materials and Methods: Female subjects with idiopathic scoliosis who were prescribed a TLSO were included in this study. Demographic and clinical data were collected from medical records on age, sex, hours of TLSO wear, body mass index (BMI), and Risser sign. Radiographic Cobb angle, data regarding curve flexibility, and the amount of coronal translation used during the CAD modification process were recorded. Differences in the primary scoliotic curve were then assessed based on initial x-rays and in-orthosis x-rays to calculate the change in Cobb angle, apical vertebra translation (AVT), coronal balance (CB), and thoracic trunk shift (TTS). Results: Seventeen participants were included in the study. Average measured curve flexibility was 59.64%, and applied coronal translation to the CAD model ranged from 3 to 19 mm. Average Cobb angle improvement from the initial x-ray to the first in-orthosis x-ray was 23.57%, which was statistically significant ( P < 0.01). Average improvement of AVT was 6.52 mm, which was statistically significant ( P < 0.05). CB improved by an average of 5.29 mm, and TTS improved by an average of 2.33 mm, neither of which was found to be a statistically significant improvement. No correlation was found between applied shifting in CAD modifications and Cobb angle improvement, AVT improvement, CB improvement, or TTS improvement. Conclusions: These results do not support the hypothesis that greater applied lateral shifting in TLSO CAD modifications leads to greater coronal scoliotic curve correction. Orthotists are not able to predict in-orthosis coronal curve correction based on CAD modifications, spinal flexibility, and BMI alone. Additional factors play a role in the complexity of AIS treatment.